Effect of hydrogen charging on the stability of SAE 10B22 steel surface in alkaline solutions - Modiano, S.; Carreno, J. A.; Fugivara, Cecilio Sadao [UNESP]; Benedetti, Assis Vicente [UNESP]; Mattos, O. R. (Elsevier B.V., 2005)
The influence of hydrogen charging into a quenched and tempered boron steel membrane electrode (SAE 10B22) was studied using borate buffer (pH 8.4) and NaOH solutions (pH 12.7), with or without the addition of 0.01 M EDTA. At the hydrogen input side, hydrogen charging influenced cyclic voltammograms increasing the anodic charge of iron(II) hydroxide formation, and decreasing the donor density of passive films. These results suggest that the hydrogen ingress caused instability of metallic surface, increasing the surface area activity. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: boron-alloyed steel; hydrogen charging; Mott-Shottky plots; cyclic voltammetry; EIS